Permasalahan Dan Tindakan Pemerintah Indonesia Dalam Pemulihan Kondisi Keuangan Negara Pasca Pandemi Covid-19 - Putri, Najwa Ananda; Putri, Ira Septika; Aini, Putri Nurul (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
The Covid-19 pandemic had a huge impact on various sectors in Indonesia, including the economic sector. During the COVID-19 pandemic, there has been a significant decline in Indonesia's economic growth from 2019 to 2020, This is caused by the limited space for people to move around for social economic activities, which has an impact on decreasing supply or market balance in Indonesia itself. In response to this, Indonesia needs several methods to rebalance the market balance, especially from the household sphere, that is providing Social Security for former employees who have been laid off during the Covid-19 pandemic era. Not only in empowering workers who have been laid off several policies must be taken into consideration by the government and society, especially in re-stabilizing the country's economic flow. In this paper, the data collection method used is a qualitative research method with a normative juridical approach which is based on applicable legal rules and norms to be able to determine the results of problems based on the cases. The purpose of this writing is to find out the Indonesian government's solution to recovering the country's financial condition after the Covid-19 pandemic. The result of this paper can be concluded that there are national financial problems that arise as a result of the Covid-19 Pandemic causing economic losses, and the weakening of the rupiah exchange rate during the Pandemic. In terms of restoring the state's financial condition, the government took several steps by implementing an allocation policy, a Distribution Policy which is carried out by providing BLT or through social programs and providing more stimulation for the MSMEs community, and also do Stabilization Policy.